2007
DOI: 10.1007/s00246-007-9126-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Right Ventricular Contraction by Myocardial Strain in Children Using a Two-Dimensional Tissue Tracking Method

Abstract: Two-dimensional tissue tracking makes it possible to detect myocardial strain in any direction. Consequently, this method is applicable for evaluation of myocardial dyssynchrony. This study enrolled 22 healthy volunteers (11 boys and 11 girls) ages 1.6 to 10.8 years (mean, 6.8 years). Echocardiography (subxiphoid right anterior oblique view) of the right ventricle was examined. Three tracking points were put on the right ventricle, and time-strain curves of the inflow tract (strain at the inlet) and the outflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…However, in the longitudinal direction the peristalsis-like pattern was not observed 21 22. These findings were recently confirmed by Matsui and coworkers 7. The authors assessed longitudinal shortening at the RV free wall and at the RV outflow tract with two-dimensional tissue tracking in healthy volunteers.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, in the longitudinal direction the peristalsis-like pattern was not observed 21 22. These findings were recently confirmed by Matsui and coworkers 7. The authors assessed longitudinal shortening at the RV free wall and at the RV outflow tract with two-dimensional tissue tracking in healthy volunteers.…”
Section: Discussionsupporting
confidence: 60%
“…From an anatomical and embryological perspective, the RV can be divided into two sections: the sinus (inlet) and the infundibulum (outlet) 5 6. Previous studies have demonstrated the presence of temporal differences in motion between the RV inlet and outlet in patients with cToF as well as in healthy subjects 4 7. However, characterisation of the RV mechanical activation sequence with different imaging techniques provided conflicting data 4 7 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TDI allows regional myocardial velocities and systolic and diastolic intervals to be measured (29, 30). Therefore, TDI is superior and more sensitive than conventional echocardiography for detecting subclinical abnormalities in RV (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RV function cannot easily appraisable because RV is a triangle-shaped chamber composed of the inlet portion, the outlet portion, and the apical portion with rough trabeculations having a complex architecture. For these reasons, RV global and regional function can be more entirely evaluated with speckle-tracking method [42].…”
Section: Strain and Strain Rate Imagingmentioning
confidence: 99%